2013
DOI: 10.1007/s12264-013-1305-3
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of morphine and dopaminergic compounds on spatial working memory in rhesus monkeys

Abstract: Opiates and dopamine (DA) play key roles in learning and memory in humans and animals. Although interactions between these neurotransmitters have been found, their functional roles remain to be fully elucidated, and their dysfunction may contribute to human diseases and addiction. Here we investigated the interactions of morphine and dopaminergic neurotransmitter systems with respect to learning and memory in rhesus monkeys by using the Wisconsin General Test Apparatus (WGTA) delayed-response task. Morphine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…The lowest dose VPA group showed more significant changes compared to higher doses under these ASD-like behavioral assays, which may be due to the elevated VPA doses having greater potential for toxic effects. An additional reason may be the non-monotonic neurobehavioral effects which have previously been observed for many classes of compounds, such as endocrine disruptors (Lagarde et al, 2015), or dopaminergic compounds (Wang, J.-H. et al, 2013). The reason may arise from numerous molecular mechanisms such as opposing effects, receptor desensitization, negative feedback with increasing dose, or dose-dependent metabolism modulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest dose VPA group showed more significant changes compared to higher doses under these ASD-like behavioral assays, which may be due to the elevated VPA doses having greater potential for toxic effects. An additional reason may be the non-monotonic neurobehavioral effects which have previously been observed for many classes of compounds, such as endocrine disruptors (Lagarde et al, 2015), or dopaminergic compounds (Wang, J.-H. et al, 2013). The reason may arise from numerous molecular mechanisms such as opposing effects, receptor desensitization, negative feedback with increasing dose, or dose-dependent metabolism modulation.…”
Section: Discussionmentioning
confidence: 99%
“…The distance moved after touching was scored manually with one perimeter of the well as 1 mm, and a semiquantitative assessment of one to three quarters of the well as 0.25, 0.5 and 0.75 mm. There were a total of 30 embryos in each treatment group from three biological repeats that were used for data analysis with methods previously described in detail (Wang, X. et al, 2013; Yang et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…While the small sample size is a limitation of this study because the pilot studies are often used before larger studies. In addition, individual differences in rhesus monkeys have been shown with small sample sizes in previous behavioral studies53132 in order to provide a foundation for further work with larger sample populations.…”
Section: Discussionmentioning
confidence: 99%
“…Three out of the four articles identified for bromocriptine concluded that bromocriptine led to improved working memory in different types of maze tests [ 23 , 24 , 25 ]. The fourth study analyzed the effects of bromocriptine on memory-depleted rhesus monkeys and the authors concluded that bromocriptine impaired working memory both individually and paired with morphine [ 26 ]. Tarantino et al [ 23 ], compared the effects of a SKF 38393, a D1 receptor agonist, with the effects of bromocriptine on working memory and reference memory in 12 mice.…”
Section: Resultsmentioning
confidence: 99%